1991
DOI: 10.1083/jcb.115.4.949
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to detect toxin-catalyzed ADP-ribosylation in intact cells: its use to study the action of Pasteurella multocida toxin.

Abstract: Abstract. Certain microbial toxins are ADP-ribosyltransferases, acting on specific substrate proteins. Although these toxins have been of great utility in studies of cellular regulatory processes, a simple procedure to directly study toxin-catalyzed ADPribosylation in intact cells has not been described . Our approach was to use [2?H]adenine to metabolically label the cellular NAD+ pool. Labeled proteins were then denatured with SDS, resolved by PAGE, and detected by fluorography. In this manner, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…The concentration of pertussis toxin required to block PKC activation has previously been demonstrated to ADPribosylate a 40-kDa G i protein in intact Swiss 3T3 cells (47 raf-1 activation in MEF. Confluent secondary cultures of MEF were treated with 10 M SPC or 20 ng/ml PDGF for 3 min and lysed; p74 raf-1 activity was then assayed as described under "Experimental Procedures."…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of pertussis toxin required to block PKC activation has previously been demonstrated to ADPribosylate a 40-kDa G i protein in intact Swiss 3T3 cells (47 raf-1 activation in MEF. Confluent secondary cultures of MEF were treated with 10 M SPC or 20 ng/ml PDGF for 3 min and lysed; p74 raf-1 activity was then assayed as described under "Experimental Procedures."…”
Section: Discussionmentioning
confidence: 99%
“…Since NAD ϩ is a membrane-impermeant compound, it must either be injected into the cell or metabolically radiolabeled in order to study endogenous ADP-ribosylation. It has been previously shown that the labeling with [ 3 H]adenine permits the study of toxin-catalyzed G proteins ADP-ribosylation in intact cells (30) and the in vivo ADPribosylation of GRP78/BiP protein (49). Thus the mono-ADPribosylation of the ␤ subunit was analyzed by in vivo labeling of intact CHO cells employing [ 3 H]adenine to label metabolically the cellular NAD ϩ pool, followed by separation of the labeled ␤ subunit with an affinity column (Fig.…”
Section: Identification Of a 36-kda Adp-ribosylated Protein As The Gmentioning
confidence: 99%
“…PMT is encoded as a 146 kDa singlechain bacterial protein, which shares partial homology with the multinucleating toxins, cytotoxic necrotising factors types 1 and 2 (CNF-1, CNF-2), produced by some strains of E. coli [10,11]. Although PMT contains a putative ADP-ribosylation motif [6], recent data have shown that PMT is unlikely to ADP ribosylate its substrate [12,13]. There is evidence that PMT facilitates the coupling of a G protein to PI-PLC [14].…”
Section: Introductionmentioning
confidence: 99%